2009
DOI: 10.1007/s10597-009-9234-3
|View full text |Cite
|
Sign up to set email alerts
|

Mediated Learning Experience Intervention Increases Hope of Family Members Coping with a Relative with Severe Mental Illness

Abstract: Forty nine family members who participated in the "Keshet" program for 6 months comprised the experimental group. The control group comprised 22 family members who underwent no structural intervention. Hope was measured at baseline and after 6 months using the Hope Scale developed by Snyder. No difference in self-perception was detected in Hope Scores between groups. However, the experimental group displayed a significant increase in their hope toward the ill relative with a concomitant decrease in the gap bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…People with mental illnesses have been at the forefront of promoting recovery attitudes, and research suggests that more individuals with psychiatric disabilities are understanding and endorsing this perspective . Family members have more recently joined the movement (D. Redlich, Hadas-Lidor, Weiss, & Amirav, 2010). Service providers seem to be late in recognition and agreement (Peebles et al, 2009;Tsai, Salyers, & Lobb, 2010).…”
Section: Addressing the Public Stigma Of Mental Illnessmentioning
confidence: 99%
“…People with mental illnesses have been at the forefront of promoting recovery attitudes, and research suggests that more individuals with psychiatric disabilities are understanding and endorsing this perspective . Family members have more recently joined the movement (D. Redlich, Hadas-Lidor, Weiss, & Amirav, 2010). Service providers seem to be late in recognition and agreement (Peebles et al, 2009;Tsai, Salyers, & Lobb, 2010).…”
Section: Addressing the Public Stigma Of Mental Illnessmentioning
confidence: 99%
“…In this context, hope to be the best predictor for resilience was in line with the literature suggesting that hope encourages resilience (Benard, 1999;Brooks, 2006;Gizir, 2004;Masten, 2001;Ong, Edwards, & Bergeman, 2006;Synder et al, 2000). Moreover, hope is a protective factor for human adaptation, and for psychotherapeutic change (Magaletta & Oliver, 1999;Hayes et al, 2007), being consistently identified as a key factor in psychological counseling by client, family members and therapists in various settings (Schrank, Stanghellini, & Slade, 2008;Redlich, Hadas-Lidor, Weiss, & Amirav, 2010). …”
Section: Hopementioning
confidence: 99%
“…Each item is answered using an eightpoint, Likert-type scale, ranging from 'definitely false' to 'definitely true'. The AHS has also established psychometric properties across different cultures and is available in the public domain [33,34].…”
Section: Protective Personality Characteristicsmentioning
confidence: 99%